2018
DOI: 10.1007/s11432-017-9279-3
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo-random sequence generation scheme based on RNS and permutation polynomials

Abstract: Long period pseudo-random sequence plays an important role in modern information processing systems. Base on residue number system (RNS) and permutation polynomials over finite fields, a pseudorandom sequence generation scheme is proposed in this paper. It extends several short period random sequences to a long period pseudo-random sequence by using RNS. The short period random sequences are generated parallel by the iterations of permutation polynomials over finite fields. Due to the small dynamic range of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In our method, the requirement of same polynomial for each residue channel is not necessary. The performance evaluations for the chaotic sequence in [17] showed that our generation method has similar random performance with that of Harris company. However, our method has more flexible choices in polynomial construction.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…In our method, the requirement of same polynomial for each residue channel is not necessary. The performance evaluations for the chaotic sequence in [17] showed that our generation method has similar random performance with that of Harris company. However, our method has more flexible choices in polynomial construction.…”
Section: Introductionmentioning
confidence: 79%
“…As a result, a higher sequence generation rate can be achieved, leading to higher efficiency of the image encryption system. In [17], we have presented the sequence generation method, polynomial construction method, performance evaluations and hardware implementation structure in detail. Compared with the method of Harris Corporation, the construction of iteration polynomials in [17] is more flexible.…”
Section: Generation Methods Of Chaotic Sequences Based On Rns and mentioning
confidence: 99%
See 2 more Smart Citations
“…Carrying out simulation analysis, which establishes models to assess different algorithms' performances in most situations, is crucial before the actual flight test. In this section, the total differential method and Monte Carlo method will be discussed as the error analysis methods [74][75][76][77][78][79][80][81][82][83][84][85][86][87].…”
Section: Simulation Analysis Methods and Evaluation Index Of Position...mentioning
confidence: 99%